OPTIMIZING CUSTOMER DECISION-MAKING FOR DAIRY FMCG IN INDONESIAN MINIMARKETS (CASE PT. ZUZHU INDONESIA) - Devita Putri Saraswati; Prawira Fajarindra Belgiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research examines the optimization of customer decision-making processes for dairy FMCG in Indonesian minimarkets, using PT. Zuzhu Indonesia as a case study. With the rising competition in Indonesia's dairy market, the study focuses on how promotions, channels, product displays, and cashier recommendations affect purchasing behaviors. The primary research objective is to understand how those factors influence customer purchase decisions. Additionally, the study aims to identify the stages of the purchasing journey and propose strategies to enhance sales performance in the competitive market. Using qualitative descriptive methods, data was collected through semi-structured interviews and observations. Analysis shows promotions attract price-sensitive and non-loyal customers, particularly for bulk purchases. Customers favor online shopping for planned purchases and offline shopping for immediate needs, with impulse buys influenced by strategic product placement and cashier recommendations. Non-loyal customers are more likely to switch brands based on in-store promotions and product visibility, while loyal customers prefer online shopping due to convenience and trust in the brand. Zuzhu Indonesia can enhance minimarket performance by securing prominent in-store placements, expanding product listings, and using targeted promotions like bulk purchasing deals online. Non-price promotions, such as loyalty programs and strong brand messaging, can help to differentiate in a crowded market.